Jordan derivations of polynomial rings - Lishchynsky, I.I. (Carpathian Mathematical Publications, 2009)
We study connections between the set of Jordan derivations of a ring R and the sets of Jordan derivations of a polynomial ring R[x_1,…,x_n] and formal power series ring R[[x_1,…,x_n]]. We also establish a condition when JDer R is a left R-module.